2019
DOI: 10.3390/microorganisms7030062
|View full text |Cite
|
Sign up to set email alerts
|

Editorial for the Special Issue: Thermophiles and Thermozymes

Abstract: Heat-loving microorganisms or thermophiles arouse noticeable scientific interest nowadays, not only with the aim to elucidate the mystery of life at high temperatures, but also due to the huge field of biotechnological applications of the enzymes they produce or thermozymes, able to function under industrial harsh conditions [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The biochemical and structural analyses have revealed that thermostability is imparted by the concerted action of different structural features rather than a single unique feature ( Cobucci-Ponzano et al, 2010 ). Various stabilization factors such as a lower number of loops and cavities, increased number of ion pairs, large number of solvent molecules buried in cavities of the protein core, a higher number of proline residues in loops, a reduced ratio of protein surface area to protein volume, greater degree of oligomerization and an increased hydrophobic interactions have been predicted for the enhanced thermostability of thermozymes ( González-Siso, 2019 ). The composition of amino acids is also a determining factor in thermostability of enzymes.…”
Section: Factors Governing Thermostability and Kinetics Of Cellulasesmentioning
confidence: 99%
“…The biochemical and structural analyses have revealed that thermostability is imparted by the concerted action of different structural features rather than a single unique feature ( Cobucci-Ponzano et al, 2010 ). Various stabilization factors such as a lower number of loops and cavities, increased number of ion pairs, large number of solvent molecules buried in cavities of the protein core, a higher number of proline residues in loops, a reduced ratio of protein surface area to protein volume, greater degree of oligomerization and an increased hydrophobic interactions have been predicted for the enhanced thermostability of thermozymes ( González-Siso, 2019 ). The composition of amino acids is also a determining factor in thermostability of enzymes.…”
Section: Factors Governing Thermostability and Kinetics Of Cellulasesmentioning
confidence: 99%
“…However, harsh conditions required for many industrial processes-such as high temperature and/or the use of organic (co)solvents-may impede the use of some enzymes. To address these drawbacks, using thermotolerant biocatalysts obtained from thermophilic organisms is an excellent alternative [20][21][22][23], as these thermozymes can efficiently work at very high temperatures [24,25] and are generally very resistant to organic solvent-promoted denaturation [26,27]. Among all the arsenal of enzymes available for being used in biotransformations, lipases (triacylglycerol hydrolases, EC 3.1.1.3) are one of the most frequently applied, as they are easily available, do not need cofactors and display a wide range of substrate recognition [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence and structural characteristics such as presence of insertions and deletions, proline substitutions, closer packing of water-accessible surface residues, and increase in helical contents and hydrogen bonds has also been suggested to contribute towards increase in the thermostability of thermophilic proteins [14][15][16]. Evidently, the characteristics providing thermostability to proteins can exist in various forms, and further understanding protein features and characteristics that likely contribute towards the thermostability of proteins is of much interest [13,17].Within the domain Bacteria, hyperthermophilic organisms are mainly present in three bacterial phyla viz. Aquificae, and Thermotogae [4,9,[18][19][20][21].…”
mentioning
confidence: 99%